Integrating Technology to Enhance Teaching and Learning: A Mixed-Methods study (International Journal of Scientific Research in Science and Technology, 2025)
Integrating technology into teaching and learning environments promises to improve student engagement, personalize instruction, and support deeper learning. This manuscript reports a mixed-methods study that evaluates the effects of a structured technology-integration intervention across undergraduate engineering courses. The intervention—framed by the Technological Pedagogical Content Knowledge (TPACK) model and the SAMR taxonomy—combined learning management system (LMS) enhancements, adaptive quizzes, interactive simulations, and collaborative cloud-based assignments. Quantitative results from pre/post assessments (n = 214) show a statistically significant improvement in conceptual understanding (Cohen’s d = 0.48, p < 0.01). Qualitative data from focus groups and instructor interviews (n = 24) revealed increased student motivation, better formative feedback, and challenges related to training and access. The paper concludes with practical guidelines for engineering departments to plan, implement, and evaluate technology integration at scale.